EFFICACY OF TELMISARTAN AND ATENOLOL IN MANAGEMENT OF ESSENTIAL HYPERTENSION - Khan, Purdil; Khan, Wasil; Abbasi, Abdullah; Ahad, A.; Khan, Momin; Ahmad, Yasir; Ahmad, Aziz (Journal of Ayub Medical College Abbottabad, 2012)
Background: Telmisartan and atenolol are widely used in the management of essential hypertension. This study was conducted to compare the efficacy of these two drugs in management of patients of essential hypertension. Methods: Diagnosed patients of essential hypertension were selected. Therapeutic option (telmisartan/atenolol) was allocated to the patients by lottery method and they were divided into two groups. The patients were followed on subsequent visits (4 in total) and their sitting systolic and diastolic blood pressures were recorded. Results: Total number of 180 patients were divided into two treatment groups (i.e., telmisaran and atenolol). Forty percent were male and 60% were female. Majority of the patients were of age group 56-75 years. Telmisartan reduced systolic and diastolic blood pressure significantly compared to atenolol at the end of 8 weeks of treatment (p=0.000 and 0.016 respectively). Conclusion: Telmisartan 80 mg once daily is more effective than atenolol 50 mg once daily in lowering systolic and diastolic blood pressure at the end of 8 weeks of treatment. Keywords: Telmisartan, Angiotensin II receptor blocker, atenolol, beta blocker, hypertension